ANGIOTENSIN II RECEPTOR ANTAGONISTS AND ACE INHIBITORS: OPTIMIZATION OF CHOICE FOR TREATMENT OF CARDIOVASCULAR DISEASES - E. M. Khurs; A. V. Poddubnaya (Столичная издательская компания, 2016)
Aim. To evaluate the cardioprotective effects of ACE inhibitor, ramipril and angiotensin II receptor antagonist (ARA), valsartan at the cardiovascular continuum (CVC) stages.Material and methods. 577 patients were examined. Patients with arterial hypertension (HT) (n=283; group 1), with metabolic syndrome (n=137; group 2), with HT associated with ischemic heart disease (n=157; group 3) were randomized into treatment subgroups A (ramipril) and B (valsartan). All patients had clinical examination, transthoracic echocardiography with remodeling indexes calculation, ambulatory blood pressure monitoring initially and after 6 months of therapy.Results. Valsartan had priority in prevention of early cardiac remodeling (reduction in left ventricular (LV) hypertrophy and myocardial stress, improvement of functional heart parameters) at early CVC stage (HT, metabolic syndrome). On the other hand ramipril had priority at advanced stage of CVC (reduction in systolic diameter-thickness ratio, LV hypertrophy, myocardial stress and myocardial stiffness). At the advance stage of CVC valsartan treatment also resulted in significant reduction in LV hypertrophy and myocardial stress, improvement in cardiac remodeling functional parameters but had no effect on LV diameter-thickness ratio.Conclusion. The ARA treatment is preferred at early CVC stage for better cardioprotection.